Vietnamese current e-commerce and opportunities for human resources training in educational institutions - Phan Thị, Thúy; Thùy Dung, Lê Vũ (Tay Nguyen Journal of Sciences, 2024)
E-commerce has developed rapidly worldwide over the past two decades, and Vietnam is now experiencing its first decade of significant growth. This study aims to assess the current state of E-commerce (EC) development and the demand for human resources by Vietnamese enterprises. The study also identifies opportunities for human resource training activities in educational institutions, particularly through formal training programs. Data from the Department of E-commerce and Digital Economy and the Vietnam E-commerce Association (2021-2023), and various previous reports and studies is based to analyse. Using descriptive statistical methods, the study reveals that the development and application of EC in enterprises, is diverse and has been continuously increasing over the years. However, enterprises face a shortage of high-tech personnel. Futhermore, human resource training in educational institutions remain limited. This situation, thus, presents an opportunity to expand training programs and courses to better meet the needs of society and enterprises.